Dendrobium officinale polysaccharide attenuates type 2 diabetes in mice model by modulating gut microbiota and alleviating intestinal mucosal barrier damage - Xiaoxia Chen; Chun Chen; Changyang Ma; Wenyi Kang; Junlin Wu; Xiong Fu (Food Science and Human Wellness)
The purpose of this study was to investigate the hypoglycemic effect and mechanism of Dendrobium officinale polysaccharide (DOP) on type 2 diabetes mellitus (T2DM) mice established by high-fat diet and streptozotocin. The results showed that DOP improved glycolipid metabolism and serum inflammation levels, and inhibited intestinal-derived lipopolysaccharide (LPS) translocation, suggesting that inhibiting LPS-mediated intestinal barrier damage may be a key target for DOP to alleviate T2DM. Interestingly, the study found that DOP reduced intestinal inflammation and oxidative stress levels, significantly up-regulated the mRNA expression of tight junction proteins Claudin-1, Occludin and zonula occluden-1 (ZO-1), and ameliorated intestinal epithelial damage. In addition, DOP strongly inhibited the intestinal pathogenic bacteria and LPS-producing bacteria Helicobacter, Enterococcus and Desulfovibrio with a reduction rate of 95%, 73% and 9%, respectively, and promoted the proliferation of anti-inflammatory bacteria Bifidobacterium and Lactobacillus by 139% and 8%, respectively. Taken together, the hypoglycemic effect of DOP was related to the protection of intestinal mucosal barrier, and its underlying mechanism lied in its excellent anti-inflammatory and gut microbiota-modulatory effects, providing a theoretical basis for developing DOP as a novel prebiotic in functional food for diabetes.